2018
DOI: 10.1016/j.dib.2017.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Data of expression status of miR- 29a and its putative target mitochondrial apoptosis regulatory gene DRP1 upon miR-15a and miR-214 inhibition

Abstract: Data is about the mitochondrial apoptosis regulatory framework genes PUMA, DRP1 (apoptotic), and ARC (anti-apoptotic) analysis after the employment of their controlling miRNAs inhibitors. The data represents putative conserved targeting of seed regions of miR-15a, miR-29a, and miR-214 with respective target genes PUMA, DRP1, and ARC. Data is of cross interference in expression levels of one miRNA family, miR-29a and its putative target DRP1 upon the inhibitory treatment of other miRNAs 15a and 214.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…MiR-29a protects mitochondrial structural integrity, restricts mito-DAMPs, and exerts an anti-inflammatory effect on the pathogenesis of NAFLD by targeting voltage-dependent anion channels and Bcl-2-associated X genes, whose oligomerization is involved in mPTP opening and mito-DAMPs release [193,194]. One computational analysis revealed that miR-29a targeted DRP1 [195], which suggests its potential role in regulating mitochondrial dynamics and mitophagy. MiR-29a inhibits glycogen synthase kinase-3β (GSK3β) to suppress sirtuin 1 (SIRT1)-mediated mitochondrial biogenesis, which leads to alleviation of mitochondrial proteostatic stress and UPRmt in the context of NASH [196].…”
Section: Mitochondrial Micrornas Interferencementioning
confidence: 99%
“…MiR-29a protects mitochondrial structural integrity, restricts mito-DAMPs, and exerts an anti-inflammatory effect on the pathogenesis of NAFLD by targeting voltage-dependent anion channels and Bcl-2-associated X genes, whose oligomerization is involved in mPTP opening and mito-DAMPs release [193,194]. One computational analysis revealed that miR-29a targeted DRP1 [195], which suggests its potential role in regulating mitochondrial dynamics and mitophagy. MiR-29a inhibits glycogen synthase kinase-3β (GSK3β) to suppress sirtuin 1 (SIRT1)-mediated mitochondrial biogenesis, which leads to alleviation of mitochondrial proteostatic stress and UPRmt in the context of NASH [196].…”
Section: Mitochondrial Micrornas Interferencementioning
confidence: 99%
“…Drp1 has been shown to be the target of several miRNAs including miR411, miR29a, and miR150–5p. ( Jan et al, 2018 ; Wang Z. J. et al, 2021 ; Yang W et al, 2021 ). MiRs-34 belongs to mitomiRs, consistent with the results in our study, but its role in mitochondrial function is not completely understood ( Barrey et al, 2011 ; Geiger and Dalgaard, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The p53 upregulated modulator of apoptosis (PUMA), an activator of BAX/BAK for the induction of MPT and subsequent apoptosis, can also be targeted by miR-29a [134]. Moreover, one computational analysis revealed that miR-29a targets dynamin-related protein 1 (DRP1) [135], implying its potential role in regulating mitochondrial dynamics and mitophagy. In line with the aforementioned studies, our experimental results have shown that liver protective-miR-29a can reduce BAX expression [46].…”
Section: Role Of Mir-29a In Mitochondrial Metabolismmentioning
confidence: 99%